Adventures in Chinese realism : classic philosophy applied to contemporary issues - Harris, Eirik Lang; Schneider, Henrique (Albany : State University of New York Press, 2022)
"Relates Chinese Realism to contemporary political and ethical challenges, for example in international relations and the morality of the public sector"--
Daoist realism : the challenge to the school of law in the radical Lao-Zhuang tradition and its lessons for realist theories of international relations / John A. Rapp -- The Han Feizi and the presidential bubble / Gordon B. Mower -- Han Fei and ethics in the corporate realm / Eirik Lang Harris -- Applying Han Fei's critique of Confucianism to contemporary Confucian meritocracy / Zujie Jeremy Huang -- The legal vocation of Chinese scholar-officials : a plan for reform / Kenneth Winston -- Hegemony : China's foreign policy through Han Feizian lenses / Henrique Schneider -- Politics, language, and mind in early Chinese legalist ideas : focusing on the comparison of Shen Buhai with Han Fei / Soon-ja Yang -- Chinese legalist analysis of German administrative law-tripolar action modes and reconceptualized rulership / Philipp Renninger -- Han Fei's genealogical arguments / Lee Wilson -- Amoral desert? Han Fei's theory of punishment / Eirik Lang Harris -- Ideal interpretation of political texts / Al Martinich.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 29, 2022).
JSTOR
Keywords: Han, Fei, -- -233 B.C.; Han Feizi (Han, Fei); Legalism (Chinese philosophy); Realism; Taoism; Philosophy, Chinese -- To 221 B.C.; Political science -- Philosophy; China -- Politics and government -- To 221 B.C.; Réalisme.; Taoïsme.; Philosophie chinoise -- Jusqu'à 221 av. J.-C.; Chine -- Politique et gouvernement -- Jusqu'à 221 av. J.-C.; Taoism; International Relations; China; Asia; HISTORY; Comparative; LAW; Eastern; PHILOSOPHY; Ethics & Moral Philosophy; Political; POLITICAL SCIENCE; Legalism (Chinese philosophy); Philosophy, Chinese; Political science -- Philosophy; Politics and government; Realism; Taoism; China; To 221 B.C.